Phylogenomic analysis of the hemp family (Cannabaceae) reveals deep cyto‐nuclear discordance and provides new insights into generic relationships - Fu, Xiao‐Gang; Liu, Shui‐Yin; Velzen, Robin; Stull, Gregory W.; Tian, Qin; Li, Yun‐Xia; Folk, Ryan A.; Guralnick, Robert P.; Kates, Heather R.; Jin, Jian‐Jun; Li, Zhong‐Hu; Soltis, Douglas E.; et al. (Journal of systematics and evolution : JSE, 2023)
Cannabaceae are a relatively small family of angiosperms, but they include several species of huge economic and cultural significance: marijuana or hemp (Cannabis sativa) and hops (Humulus lupulus). Previous phylogenetic studies have clarified the most deep relationships in Cannabaceae, but relationships remain ambiguous among several major lineages. Here, we sampled 82 species representing all genera of Cannabaceae and utilized a new dataset of 90 nuclear genes and 82 chloroplast loci from Hyb‐Seq to investigate the phylogenomics of Cannabaceae. Nuclear phylogenetic analyses revealed a robust and consistent backbone for Cannabaceae. We observed nuclear gene‐tree conflict at several deep nodes in inferred species trees, also cyto‐nuclear discordance concerning the relationship between Gironniera and Lozanella and the relationships among Trema s.l. (including Parasponia), Cannabis + Humulus, and Chaetachme + Pteroceltis. Coalescent simulations and network analyses suggest that observed deep cyto‐nuclear discordances were most likely to stem from incomplete lineage sorting (ILS); nuclear gene‐tree conflict might be caused by both ILS and gene flow between species. All genera of Cannabaceae were recovered as monophyletic, except for Celtis, which consisted of two distinct clades: Celtis I (including most Celtis species) and Celtis II (including Celtis gomphophylla and Celtis schippii). We suggest that Celtis II should be recognized as the independent genus Sparrea based on both molecular and morphological evidence. Our work provides the most comprehensive and reliable phylogeny to date for Cannabaceae, enabling further exploration of evolutionary patterns across this family and highlighting the necessity of comparing nuclear with chloroplast data to examine the evolutionary history of plant groups. Tanglegram showing the incongruence between the nuclear (left) and chloroplast (right) trees of Cannabaceae both inferred by partitioned RAxML analyses. Black lines connect the same taxa between the two trees. The colored branches indicate the major clades of Cannabaceae: black, outgroups; brown, Aphananthe; medium aquamarine, Gironniera; purple, Lozanella; red, Celtis II; light green, Chaetachme + Pteroceltis; green, Cannabis + Humulus; orange, Trema s.l.; and blue, Celtis I.